Implementation process of equity committees in PET-Health: Experience report (Research, Society and Development, 2025)
Introduction: The 11th edition of the Education through Work for Health Program supported projects from Higher Education Institutions focused on promoting equity. Objective: To describe the situational diagnosis activities carried out by the Federal University of Juiz de Fora – Governador Valadares Campus (UFJF-GV) in a health micro-region in Eastern Minas Gerais, aiming to support the implementation and strengthening of Municipal Equity Committees. Methods: A questionnaire was administered, and synchronous and asynchronous communication strategies were employed through messaging applications and videoconferencing platforms. The process comprised two stages: a preliminary phase and the development of the situational diagnosis. The preliminary phase involved theoretical studies on health equity and strategic alignment meetings. Subsequently, the situational diagnosis was developed, systematized in a document delivered to the municipalities, containing information on the stage of implementation of the Municipal Equity Committees and a detailed analysis of a common problem in the micro-region. Results: The preliminary phase enabled a critical and sensitive approach to the activities, aligned with equity principles. It was observed that all municipalities had formally established Equity Committees; however, civil society participation was limited or absent. The priority problem identified for the micro-region was the “operational inoperability in implementing and managing equity policies.” Conclusion: The situational diagnosis enabled a contextualized analysis of the micro-region, fostering practical and reflective learning on equity management and promotion in health. The experience contributed to student development and strengthened local initiatives aligned with the principles of Brazil's Unified Health System.